75 GENE EXPRESSION PROFILING CAN DISTINGUISH PHYSIOLOGIC B-CELL CHRONIC LYMPHOCYTIC LEUKEMIA CLONAL EXPANSIONS FROM PRELEUKEMIC AND LEUKEMIC CLONES. (1st March 2006) - McCarthy, B.; Wang, X.-P.; Paul, S.; Goodwin, L.; Rawstron, A.; Chiorazzi, N.
Abstract : B-cell chronic lymphocytic leukemia (B-CLL), the most common adult leukemia, is a clonal disease manifested by an absolute lymphocytosis. However, not all clonal lymphocytoses are B-CLL since monoclonal B-cell subpopulations can be detected in apparently healthy individuals using flow cytometry. This phenomenon is termed monoclonal B-cell lymphocytosis (MBL) or clonal lymphocytosis of uncertain significance (CLUS). CLUS has been identified in healthy volunteers with normal lymphocyte counts at a frequency of 3.5% and among first-degree relatives of B-CLL patients at a higher frequency (13.5%).* These findings suggest a transition from a B-CLL progenitor cell to overt B-CLL that occurs over time. Therefore, it would be useful, both therapeutically and mechanistically, to identify genes involved in this transition and to determine which cell population is vulnerable to leukemic progression. Using gene expression profiling, we and others have identified genes transcribed at significantly different levels between B-CLL patients and normal subjects. From these genes, a select panel was chosen, and the expression of these genes was quantified by rtQ-PCR from mRNA of patients with B-CLL as well as from normal subjects, with and without CLUS. Since the numbers of cells within the expanded clones from normal individuals with CLUS was limiting, in these instances we amplified mRNA using the Nugen OVATION RNA Amplification System. Using this rtQ-PCR approach, we accurately distinguished the clonal expansions of normal healthy subjects from those with CLUS and B-CLL. Therefore, expression of this gene panel may provide a novel way to identify genetic patterns that change during the transition from B-cell clonal expansions that occur physiologically from those that occur among preleukemic and leukemic B-cell populations. *Rawstron et al. Blood 2002;100:635-9.